THE ROLE OF ARTIFICIAL INTELLIGENCE AND DIGITAL TOOLS IN LEARNING ENGLISH. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper examines the role of artificial intelligence (AI) and digital tools in learning English as a foreign language focusing on learners from remote areas, girls, and individuals with disabilities. With the rapid development of AI technologies, learners now have access to a variety of applications and platforms that support vocabulary building, grammar practice, and communication skills. The study applies a mixed-method approach, including literature review and analysis of user experiences, to evaluate the effectiveness of tools such as ChatGPT, Duolingo, and Grammarly. Findings indicate that AI can enhance learner motivation, provide immediate feedback, and create personalized learning environments. However, challenges remain, including limited access to technology, lack of teacher training, and concerns about overreliance on automated systems.  Findings show that AI can increase learner motivation, promote independent study, and support more inclusive education. However, challenges remain, such as limited internet access in rural areas, lack of digital skills, and the need for teacher training. The study concludes that integrating AI and digital resources into English language education can reduce educational inequality and empower disadvantaged learners if implemented thoughtfully and supported by adequate infrastructure.